A Novel Multi-Level Perceptron for Accurate Heart Stroke Diagnosis - Zaman, Muhammad; Khubaib, Muhammad; Kahkashan, Tanzila; Zahoor, Anam; Shahbaz, Narges; Shoukat, Shahzad; Nisar, Fahma (Buana Information Technology and Computer Sciences (BIT and CS), 2025)
Heart is a very important part of human body, it supply blood to body. If the heart fail down the person cannot survive. This is very important to diagnose the heart disease timely to start proper treatment. To dingoes this disease manually takes time a lot and budget of the patient. Traditionally the patient have to go through form different test then he have to give medical history to the doctor then the doctor make decision about their disease and then the treatment start. In the developing countries especially like Pakistan the income of the people are too much low and they cannot offered different type of expensive tests like ECG etc. In this way the disease cannot detect timely and cannot treated properly. The heart stroke can be predicted by analyzing different attributes like blood pressure, cholesterol age etc., this is a best and easy way to predict heat stroke timely. Different types of Machine Learning and deep learning algorithms are used for heart stroke predictions. In this paper we purposed Novel MultiLayer-Perceptron (MLP) that are efficient in classification and in heart stoke prediction that model achieve high accuracy of 99%.